Transforming Pedagogical Practices: Training on Teaching Methods and Media for Islamic Educators - Hendi Sugianto; Farnela Diva; Rumia Usman; Setiyo Apriyandi (Al-Qalam Institute, 2024)
This research focuses on enhancing the pedagogical competencies of Islamic Religious Education (PAI) teachers through intensive training on innovative teaching methods and contextual media development. The main objective of this study is to explore the effectiveness of participatory training in building teachers' individual competencies and strengthening institutional culture toward continuous pedagogical innovation. This study employs a qualitative method with a Participatory Action Research (PAR) approach, actively involving teaching staff at MTs-MA Al-Khairaat Guraping, Kota Tidore. Data were collected through participatory observation, in-depth interviews, and focus group discussions, then analysed using Miles and Huberman's interactive analysis technique consisting of three stages: data reduction, data presentation, and conclusion drawing/verification. The results showed that training successfully improved teachers' theoretical knowledge from 45% to 85%, practical skills from 40% to 90%, and confidence from 50% to 80%. The implications of this study emphasize the importance of hands-on, collaborative approaches and institutional support to ensure sustainability and effectiveness of teacher professional development programs in Islamic educational institutions.